Analysis of fatty acids in egg yolks of various production systems - Nyberg, Jonatan (SLU/Department of Molecular Sciences, 2017)
OBJECTIVES: The objective of this study was to compare fatty acid composition of different eggs. Seven kinds of eggs from three companies were taken, including organic, free range, enriched and “farmer” eggs. RESULTS: In total 15 fatty acids were identified. The fatty acids with highest content found in the egg yolks were palmitic acid, steric acid, oleic acid and linoleic acid. The saturated fatty acid content was similar in all samples. Different amount of n-3 fatty acids were observed in the eggs. Uggelsta organic had highest do-cosahexaenoic acid content and Kronägg Guld Gula free range with added algae had low polyunsaturated fatty acids and low docosahexaenoic acid content. CONCLUSION: Egg yolk from organic hens with access to outdoor exercise yards appears to have a higher DHA content but this result need to be confirmed by fur-ther research.